2010
DOI: 10.1111/j.1365-2036.2010.04399.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality from peptic ulcer bleeding: the impact of comorbidity and the use of drugs that promote bleeding

Abstract: SUMMARY BackgroundUse of drugs promoting peptic ulcer bleed has increased several folds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 31 publications
3
35
0
4
Order By: Relevance
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 77%
“…The association between lower serum albumin values and higher UGIB risk is also supported by a previous study in patients with CKD receiving dialysis (19). A history of UGIB is an important risk factor but has not been taken into consideration in previous studies (1)(2)(3)6,(20)(21)(22). Our study showed that patients with CKD and a history of UGIB had a 2-fold higher risk of UGIB.…”
Section: Discussionsupporting
confidence: 77%
“…Increased risk factors include age above 65 years, concurrent use of steroid/anticoagulant therapy, or history of PU [222, 255, 267269]. Presence of relevant co-morbidities (heart failure, renal impairment, stroke, diabetes, on-going malignancy) and smoking are additional risk factors for both GI events and related mortality [255, 268270]. Standard PPI-dose is the most effective gastroprotective therapy [271, 272].…”
Section: Resultsmentioning
confidence: 99%
“…A further study in Sweden examined the records of 731 patients admitted with non-variceal GI bleeding, and reported that the mortality of 440 patients with upper GI bleeding, and 289 with lower GI bleeding was 3% in both. [59]…”
Section: Discussionmentioning
confidence: 99%